Intermittent Fasting Partially Alleviates Dietary Margarine-Induced Morphometrical, Hematological, and Biochemical Changes in Female Mice, but Not in Males - Viktoriia V. Hurza; Maria M. Bayliak; Myroslava V. Vatashchuk; Oksana M. Sorochynska; Maria P. Lylyk; Oleksandra B. Abrat; Dmytro V. Gospodaryov; Kenneth B. Storey; Volodymyr I. Lushchak (Biochemistry Research International)
Margarine is a popular high-calorie component of the Western diet and was shown to be associated with the development of metabolic syndrome. Intermittent fasting (IF) is an effective approach to improve health and prevent metabolic disorders. This study aimed to investigate the effects of margarine consumption, both ad libitum and in combination with IF regimens, using young C57BL/6J mice of both sexes. Female mice fed margarine ad libitum as a supplement to the standard diet showed significant body mass gain, reduced food intake, lower blood paraoxonase activity, and higher lipid peroxide (LOOH) levels, along with higher activities of antioxidant enzymes in the liver. Margarine-fed males showed higher food intake and had lower blood triacylglycerol levels, higher LOOH levels in adipose tissue, and lower LOOH levels in the liver than their control counterparts. When a margarine-supplemented diet was provided to mice with an IF regimen, males gained body mass faster and experienced severe metabolic changes, including elevated fasting blood glucose levels, higher total leukocyte count, triacylglycerol accumulation, and reduced glycogen levels in the liver compared to their margarine ad libitum counterparts. Females treated with margarine + IF showed a partial improvement in metabolic status and a decrease in proinflammatory markers compared to the group receiving margarine ad libitum. Hence, responses to the diets were sex-specific. Females that consumed margarine ad libitum had higher metabolic sensitivity than males. Meanwhile, IF provided some protective effects in females but worsened metabolic outcomes in males when combined with a high-fat margarine diet.